CHARACTERISATION OF NANOFIBROUS SEPARATORS FOR LITHIUM-ION BATTERIES - Musil, Michal; Pléha, David (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
Nano fibred materials ensure high porosity and relative surface area of separators. These parameters are important to improve ionic mobility between electrodes and ensure sufficient electrolyte volume in battery. These advantages make electrospinning very promising method of nanofibrous separators mass production. In this paper are described electrospinning fabrication process and discussed results of separator’s electric and electrochemical properties measurements compared with Celgard 3401.